"An Old Order Is Passing": The Rise of Applied Learning in University-Based Teacher Education during the Great Depression. Issue 3 (August 2015) - D'Amico, Diana
Abstract : From the late nineteenth century through the first decades of the twentieth century, New York City housed two contrasting models of professional education for teachers. In 1870, the Normal College of the City of New York opened in rented quarters. Founded to prepare women to teach in the city's public schools, in just ten weeks the tuition-free, all-female college "filled to overflowing" with about 1, 100 enrolled students. Based upon a four-year high school course approved by the city's Board of Education, the "chief purpose" of the college was to "encourage young women… to engage in the work of teaching in elementary and secondary schools." Vocationally oriented and focused on practical skills, the Normal College stood in contrast to the School of Pedagogy at New York University and Teachers College, Columbia University founded in 1890 and 1898, respectively. The Normal College's neighbors situated their work within the academic traditions of the university. According to a School of Pedagogy Bulletin from 1912, faculty sought to, meet the needs of students of superior academic training and of teachers of experience who are prepared to study educational problems in their more scientific aspects and their broader relations.